PELATIHAN DAN PENDAMPINGAN APLIKASI BANK SAMPAH BERBASIS WEB UNTUK PENGUATAN TATA KELOLA DI KRAPYAK BERSINAR JEPARA - Rochmanto, Decky; Wibowo, Gentur Wahyu Nyipto; Ma'arif, Syamsul (Universitas Mataram, 2025)
This community service activity was carried out to improve the management of the Waste Bank in Krapyak Bersinar through training and mentoring in the use of a web-based information system. The main problem faced by the Waste Bank is manual transaction recording, which often results in errors, data loss, and a lack of transparency. Furthermore, managers also have a limited understanding of accounting and financial management in accordance with standards. Therefore, the objective of this activity was to provide training to Waste Bank managers on the use of an information system application that can simplify transaction recording and financial reporting. The methods used in this activity included problem identification through interviews and observations, socialization regarding the importance of technology in Waste Bank management, training in the use of the web-based application, and mentoring in implementing the application. The results of the activity showed that with the web-based application, Waste Bank managers can record transactions more accurately and efficiently. In addition, the resulting financial reports are more transparent and accountable. The evaluation showed that 90% of managers found it easier to record transactions and manage customer data, and 85% reported a reduction in recording errors. In conclusion, this training and mentoring successfully improved the operational efficiency of the Waste Bank in Krapyak Bersinar, as well as increasing managers' understanding of the use of information technology for better financial management.